Consider issues tied to criminal background checks in admissions process. Issue 11 (19th January 2018) - Porter, Michael
Abstract : In the debate about whether to conduct criminal background checks in the admissions process, an institution's value of campus safety and the perception that a campus is safe bump up against the value of access to higher education. Many colleges and universities feel pressure to use criminal background checks because doing so might protect against potential liability and can also demonstrate the institution's commitment to campus safety.